Suberoylanilide Hydroxamic Acid Restores Estrogen Reduced‐cTnI Expression in Neonatal Hearts of Mice. Issue 10 (28th March 2016) - Peng, Chang; Luo, Xiaomei; Xing, Qianlu; Sun, Huichao; Huang, Xupei
ABSTRACT: Diastolic cardiac dysfunction can be caused by abnormality in cTnI expression during cardiogenesis. In this study, we investigated the effects of estrogen on the abnormal expression of cTnI in the hearts of neonatal mice and its potential epigenetic mechanisms. We then evaluated suberoylanilide hydroxamic acid (SAHA), a HDAC inhibitor, as a new target treatment of diastolic cardiac dysfunction. Postnatal day 0.5 C57BL/6 mice were injected with estrogen for 1 week, then the hearts of 7‐day‐old neonatal mice were retrieved for examination. The activities of HDAC and HAT were assayed by colorimetry, and the interaction of cTnI with HDAC5 in mice hearts were examined using chromatin immunoprecipitation assays. The expression of cTnI was tested by quantitative real‐time RT‐PCR and Western blot. Estrogen treated groups displayed a significantly increased HDAC activity in the hearts of neonatal mice while HAT activity remained unchanged. Additionally, HDAC5 was higher at the cTnI promoter, as compared to the saline treated control groups. The acetylation of histone H3K9ac on cTnI promoter significantly decreased in the hearts of neonatal mice treated with estrogen, and the expression of cTnI at transcriptional and protein levels also decreased. SAHA was shown to increase the acetylation of histone H3K9ac and upregulate the expression of cTnI . The data demonstrated that SAHA can correct cTnI expression abnormality caused by estrogen through inhibiting the binding of HDAC5 to the promoter of cTnI . J. Cell. Biochem. 117: 2377–2384, 2016. © 2016 Wiley Periodicals, Inc. Abstract : HDAC5 may play a critical role on abnormal expression of cTnI induced by estrogen and SAHA can correct the expression abnormality of cTnI caused by estrogen.